Effect of different cloning strategies in pET-28a on solubility and functionality of a staphylococcal phage endolysin - Tham, Hong Y.; Song, Adelene Ai Lian; Yusoff, Khatijah; Tan, Geok Hun (Future Science, 2020)
Endolysins have been studied intensively as an alternative to antibiotics. In this study, endolysin derived from a phage which infects methicillin-resistant Staphylococcus aureus (MRSA) was cloned and expressed in Escherichia coli pET28a. Initially, the endolysin was cloned using BamHI/XhoI, resulting in expression of a recombinant endolysin which was expressed in inclusion bodies. While solubilization was successful, the protein remained nonfunctional. Recloning the endolysin using NcoI/XhoI resulted in expression of soluble and functional proteins at 18°C. The endolysin was able to form halo zones on MRSA plates and showed a reduction in turbidity of MRSA growth. Therefore, cloning strategies should be chosen carefully even in an established expression system as they could greatly affect the functionality of the expressed protein.